Developmental expression of the 43K and 58K postsynaptic membrane proteins and nicotinic acetylcholine receptors in Torpedo electrocytes - LaRochelle, WJ (J Neurosci, 1990)
The expression of the postsynaptic 43-kDa and 58-kDa proteins and actin during development of the Torpedo marmorata electric organ was compared to that of nicotinic acetylcholine receptors (AChRs). Western blot analysis demonstrates that AChRs and proteins of 43 kDa (43K protein) and 58 kDa (58K protein) are all present prior to synaptogenesis. Subsequently, levels of all 3 synaptic proteins increase dramatically during differentiation and innervation of electrocytes. In contrast, actin is present in relatively high concentrations at early times and decreases thereafter. The equimolar ratio of AChRs and the 43K protein found in the adult electric organ is established early in development. Furthermore, the AChR and 43K protein share a common postsynaptic localization in electrocytes following synapse formation. Aggregates of the AChR that form at the ventral pole of the oval-shaped electrocytes prior to innervation, however, show no detectable immunofluorescence staining with anti-43K monoclonal antibodies. Therefore, in some cases, aggregation of AChRs occurs without the 43K protein.